PENGARUH KUALITAS AUDIT PADA HUBUNGAN MORALITAS, BUDAYA DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Agustine Dwianika; Muhd. Nuryanto Amin; Calista Setiyahadi (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
AbstractThis research aim to examine: (1) The influence of morality on tax compliance (2) The influence of culture on tax compliance .(3)The influence of tax services quality on tax compliance. And (4) The influence of audit quality, morality, tax services quality on tax compliance in Serpong Tax Office and Pondok Aren Tax Office. This study uses a quantitive approach and employs a regression model analysis by using 103 quistionare from respondents. The results of this study found that audit quality, morality, culture and tax services quality simultanesously influenced on tax compliance. Easy to pay and reporting also good and clearly informations are important for taxpayers and ultimately increase tax awareness to make taxpayers compliant and obey about tax provisions.The higher the audit quality stated on the use of Big Four KAP by taxpayers, it can increase the level of taxpayer compliance which is influenced by taxpayer morality, the culture that is understood by taxpayers and the quality of taxpayer services obtained by taxpayers.  Keyword: Audit Quality, Morality, Culture, Tax Service and Tax Compliance.